The Influence of Compensation on The Level of Job Satisfaction in The Department of Women's Empowerment, Child Protection and Binjai City Communities - Rahayu, Endah; Sugiarto, Abdi (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The purpose of this research is to determine and analyze the influence of compensation on job satisfaction at the Department of Women's Empowerment, Child Protection and Community Services in Binjai City. This research was conducted using a causal associative quantitative approach. The sample used was all employees with a total of 61 people taken using proportional sampling. The research results show that compensation has a positive and significant effect on job satisfaction. This is shown by the T-count value of T-count of 13.204 > t table 1.67109, with a significance value of 0.000 < 0.05. The regression coefficient shows that if compensation is increased by 1 unit, then job satisfaction will increase by 0.826 units assuming other variables remain constant. Apart from that, the results of the determination test show an Adjusted R Square value of 0.743 or 74.30%, which indicates that compensation has a high influence on job satisfaction, while the remaining 25.70% is influenced by other factors that have not been studied. Thus, partially, compensation has a positive and significant effect on job satisfaction in the Women's Empowerment, Child Protection and Community Services of Binjai City. This identifies that improvements in Compensation can contribute to increased job satisfaction.